Critical factors for enhancing the bioremediation of a toxic pollutant at high concentrations in groundwater: Toxicity evaluation, degrader tolerance, and microbial community. (1st January 2021) - Lin, Chi-Wen; Liu, Shu-Hui; Wu, Cheng-Fang; Chang, Shih-Hsien
Abstract: Groundwater near refinery and natural gas plants often contain elevated concentrations of toxic sulfolane. Studies on any concentration of sulfolane are limited. Column experiment was conducted to investigate the effects of adding a low dose of H2 O2 and nutrient on bioremediation. Vibrio fischeri light inhibition test was used evaluate the toxicity of effluents. The continuous column experiment conditions were sulfolane at 100 mg L −1, dissolved oxygen at 7 mg L −1, absence of phosphorus, and very short hydraulic retention time (7.9 h). A low dose of H2 O2 (5.88 mM) enhanced the sulfolane (27.1%) and COD removal (11.8%) in comparison with the control set. Adding nutrient increased bicinchoninic acid protein assay levels, sulfolane removal (99.6%) and COD removal (80.3%). Addition of both H2 O2 and nutrient further improved COD removal (90.3%) and COD/sulfolane ratio (0.90) and toxicity removal ( Vibrio fischeri light inhibition ratio < 1%). Batch experiment indicated the degraders tolerated sulfolane up to 400 mg L −1 . The DGGE method and dendrogram analysis were utilized to investigate the changes of degrader community structure. Highlights: ●Adding low-dose H2O2 and nutrient enhanced biodegradation of sulfolane in water. ●Low-dose H2O2 was a good DO source for bioremediation of sulfolane. ●Adding nutrients markedly increased microbial community density and sulfolane/COD removals. ●Sulfolane (99.5%) and COD (91.5%) were rapidly removed within a very short hydraulic retention time of 7.9 h. ●The toxicity of sulfolane effluent post-treatment was negligible (light inhibition rate < 1%).